Optimized Histological Preparation of Ovary for Ovariole Counting in Africanized Honey Bee Queens (Hymenoptera: Apidae). Issue 2 (8th March 2019) - Raulino-Domanski, Fernanda; Potrich, Michele; Freitas, Patrícia F; Abdalla, Fábio C; Martins, Elias N; Lourenco, Daniela A L; Costa-Maia, Fabiana Martins
Abstract: Techniques for counting ovariole number in virgin and mated Apis mellifera L. queens have been described in previous studies. Having a systematic and fast way to collect this measurement can help accelerate bee breeding programs, because selection decisions can be taken faster. The aim of this work was to develop an efficient histological method to preserve ovaries that allows assessing the number of ovarioles in newly emerged virgin queens, and also in mated queens, in a shorter time than the methods already published. The proposed method resulted in images suitable for ovariole counting in both newly emerged and mated queens, and the total histological process took less than 10 h. This method provides the optimization of the histological procedure for research breeding programs that use ovariole number as selection criteria for improving reproduction and production traits.